Are brain MRI abnormalities associated with the semiology of functional seizures?. Issue 2 (9th January 2023) - Asadi‐Pooya, Ali A.; Kerr, Wesley T.; Karakis, Ioannis; Kanemoto, Kousuke; Daza‐Restrepo, Anilu; Farazdaghi, Mohsen; Horbatch, Faith J.; Beimer, Nicholas J.; Eliashiv, Dawn E.; Risman, Aida; Sugimoto, Yuko; Giagante, Brenda
Abstract: Purpose: To investigate whether radiologically apparent brain magnetic resonance imaging (MRI) abnormalities are associated with the functional seizure (FS) semiology. Methods: All patients with a diagnosis of FS at the epilepsy centers at Shiraz University of Medical Sciences, Iran; Aichi Medical University Hospital, Japan; University of Michigan, USA; University of California, Los Angeles, USA; Emory University School of Medicine, USA; and Hospital el Cruce, Argentina, were studied. Results: One hundred patients were included; 77 (77%) had motor functional seizures. Lobar location of brain abnormality did not have an association with the semiology ( p  = .83). There was no significant difference between ictal behaviors in patients with frontal or parietal lesions compared to those with temporal or occipital lesions. Conclusion: There were no associations between functional seizure ictal behaviors and locations of the radiologically apparent brain MRI abnormalities. Further studies are needed to evaluate the underpinnings of varying behaviors in FS.